INFLUENCE OF HYDRODYNAMIC FLOWS ON THE OPTICAL PROPERTIES OF HYBRID ALIGNED NEMATIC LIQUID CRYSTALS - Petrosyan, K.A. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2018)
In this work we study the influence of hydrodynamic flows on the optical properties of hybrid aligned nematic liquid crystals (NLC) structure caused by direct volume expansion mechanism for the case, when the direction of flow velocity is perpendicular to the angular distribution of the molecules in the cell. It has been shown that the hydrodynamic flow leads to reorientation of NLC molecules. The behavior of the polarized light passing through the NLC layer for two opposite directions of the flow was observed.
Keywords: nematic liquid crystals; hydrodynamics; hybrid alignment; light-induced reorientation